Non-functional cervical paraganglioma in an adult: A case report - Balineni, Pradeep; Pathivada, Sandeep; Merlin, Samuel Dev; Kamal, Shruthi (Indian Journal of Case Reports, 2019)
Paragangliomas are rare neuroendocrine tumors. The most common site is the adrenals cervical region. Cervical paragangliomasare divided into carotid body and vagus types. Here, we report the case of a non-functional cervical paraganglioma in a 78-yearoldmale came with complaints of swelling in the left side of the neck for 2 years. On imaging, guided core needle biopsy showedeosinophilic cells with vacuolated nuclei and some inclusion bodies which suggested a possible clear cell tumor, neuroendocrinetumor or a paraganglioma. Complete surgical excision was done under general anesthesia, postoperative histopathology andimmunohistochemistry markers (S100, Synaptophysin, and Ki67) suggested of paraganglioma.